The Econometrics of Individual Risk : Credit, Insurance, and Marketing - Gourieroux, Christian, 1949-; Jasiak, Joann, 1963- (Book collections on Project MUSE., 2011)
The individual risks faced by banks, insurers, and marketers are less well understood than aggregate risks such as market-price changes. But the risks incurred or carried by individual people, companies, insurance policies, or credit agreements can be just as devastating as macroevents such as share-price fluctuations. A comprehensive introduction, The Econometrics of Individual Risk is the first book to provide a complete econometric methodology for quantifying and managing this underappreciated but important variety of risk. The book presents a course in the econometric theory of individual.